Dari Netflix Ke Negeri Gingseng: Komunikasi Budaya dan Pariwisata dalam Film 20th Century Girl - Bella Afithreea Sari; Putri Dara Maulina; Aurahaliza Mega Narwastu; Andien Ayu Valentina Putri; Arsih Amalia Chandra Permata; Wiyata Wiyata (Institut Nalanda, 2025)
In the context of globalization, film functions as a strategic medium for cultural exchange and the reinforcement of national identity. This study investigates 20th Century Girl (2022), a South Korean film distributed by Netflix, as a vehicle for intercultural communication and film-induced tourism. Employing a descriptive qualitative method and content analysis, the paper explores how narrative nostalgia, thematic depth, and cultural representation generate emotional engagement and stimulate interest in South Korea as a travel destination. The study also highlights the pivotal role of Netflix in globalizing Korean audiovisual content and strengthening the Korean Wave (Hallyu). Findings indicate that the film not only illustrates essential Korean cultural values such as the importance of friendship, family, and school traditions but also indirectly showcases cultural tourism assets, including filming locations and local lifestyles. These insights affirm the significance of cinema as a tool of cultural diplomacy and soft power for enhancing South Korea’s image on the global stage.